Petrology and trace element geochemistry of Tissint, the newest shergottite fall. (18th December 2014) - Balta, J. Brian; Sanborn, Matthew E.; Udry, Arya; Wadhwa, Meenakshi; McSween, Harry Y.
Abstract The fall and recovery of the Tissint meteorite in 2011 created a rare opportunity to examine a Martian sample with a known, short residence time on Earth. Tissint is an olivine‐phyric shergottite that accumulated olivine antecrysts within a single magmatic system. Coarse olivine grains with nearly homogeneous cores of Mg# >80 suggest slow re‐equilibration. Many macroscopic features of this sample resemble those of LAR 06319, including the olivine crystal size distribution and the presence of evolved oxide and olivine compositions. Unlike LAR 06319, however, no magmatic hydrous phases were found in the analyzed samples of Tissint. Minor and trace element compositions indicate that the meteorite is the product of closed‐system crystallization from a parent melt derived from a depleted source, with no obvious addition of a LREE‐rich (crustal?) component prior to or during crystallization. The whole‐rock REE pattern is similar to that of intermediate olivine‐phyric shergottite EETA 79001 lithology A, and could also be approximated by a more olivine‐rich version of depleted basaltic shergottite QUE 94201. Magmatic oxygen fugacities are at the low end of the shergottite range, with log fO2 of QFM‐3.5 to ‐4.0 estimated based on early‐crystallized minerals and QFM‐2.4 estimated based on the Eu in pyroxene oxybarometer. These values are similarly comparable to other depleted shergottites, including SaU 005 and QUE 94201. Tissint occupies a previously unsampled niche in shergottite chemistry: containing olivines with Mg# >80, resembling the enriched olivine‐phyric shergottite LAR 06319 in its crystallization path, and comparable to intermediate olivine‐phyric shergottite EETA 79001A, depleted olivine‐phyric shergottite DaG 476, and depleted basaltic shergottite QUE 94201 in its trace element abundances and oxygen fugacity. The apparent absence of evidence for terrestrial alteration in Tissint (particularly in trace element abundances in the whole‐rock and individual minerals) confirms that exposure to the arid desert environment results in only minimal weathering of samples, provided the exposure times are brief.